Silver bullet [videorecording (DVD)] - King, Stephen, 1947-; Busey, Gary; McGill, Everett; Haim, Corey, 1971-2010; King, Stephen, 1947- (Paramount Pictures, 2017)
Something is killing off townsfolk in Tarker's Mills. Something mysterious. Something ingenious. Something remotely human. But the only person in town with courage to stop this lurking menace is a thirteen-year-old boy, confined to a wheelchair since birth.